If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 4x + 4 + 8 = 3x + 3 + 10x Reorder the terms: 4 + 8 + 10x + 4x = 3x + 3 + 10x Combine like terms: 4 + 8 = 12 12 + 10x + 4x = 3x + 3 + 10x Combine like terms: 10x + 4x = 14x 12 + 14x = 3x + 3 + 10x Reorder the terms: 12 + 14x = 3 + 3x + 10x Combine like terms: 3x + 10x = 13x 12 + 14x = 3 + 13x Solving 12 + 14x = 3 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 12 + 14x + -13x = 3 + 13x + -13x Combine like terms: 14x + -13x = 1x 12 + 1x = 3 + 13x + -13x Combine like terms: 13x + -13x = 0 12 + 1x = 3 + 0 12 + 1x = 3 Add '-12' to each side of the equation. 12 + -12 + 1x = 3 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = 3 + -12 1x = 3 + -12 Combine like terms: 3 + -12 = -9 1x = -9 Divide each side by '1'. x = -9 Simplifying x = -9
| 4+7z=20+-3z | | 7x+3x-5x= | | x+2(x+4)=39 | | 9-1=b | | (21b-7)-5(4b+4)=-5 | | 7x-(x+4)-(2x+1)=10 | | Y=3x+1+3 | | Y=3x+1+1 | | 7y+7/3=4 | | 5x+-10=9x+26 | | -10+7x+1=46 | | 75=3(-10t-3)+5t | | 5t=42-t | | 2a=20-2a | | 28x+12=21+19x | | (110-8x)=3x | | f(41f-43)=0 | | 3(3x+7)=18 | | -7(6+8n)=-14 | | n^2+n+12=0 | | 425+25x=275+30y | | 1/5z+z+9=-9 | | 9x=9x+12 | | x^2+3x-2=x | | X=14x+1500 | | ln(3)+ln(x)=8.94 | | f(x)=-6x-10 | | x(m+6)+y(m-7)=z(m-9) | | 2n^2+2n+18=0 | | 18n+3+5n=-181 | | 6w-4x=3w+9x | | 2-5r=17 |